An evidence-based review of the epidemiology of myopic traction maculopathy - Cheong, Kai Xiong; Xu, Lingqian; Ohno-Matsui, Kyoko; Sabanayagam, Charumathi; Saw, Seang Mei; Hoang, Quan V. (Survey of ophthalmology, 2022)
Myopic traction maculopathy (MTM), one of the complications of pathologic myopia, is a spectrum of pathological conditions that are attributed to tractional changes in the eye characterized by retinoschisis, lamellar or full thickness macular hole, and foveal retinal detachment. Considering the global public health burden of MTM and pathologic myopia, it is important to understand these sight-threatening complications and their associations. We conducted an evidence-based review of the prevalence and natural history of MTM and associated risk factors. The prevalence of MTM in the general population is low, but is increased among high myopes. MTM is associated with preretinal tractional structures, myopic refractive error and axial elongation, posterior staphyloma, dome-shaped macula, chorioretinal atrophy, and myopic macular degeneration. The clinical course of MTM tends to be stable; however, MTM may progress, resulting in visual acuity deterioration, although spontaneous improvement also occurs. The associations of MTM progression include vitreous traction, location, and extent of MTM, and lamellar macular hole-specific factors. More high-quality population-based studies that assess MTM prevalence and natural history are needed.